The role of plasmonic metal-oxides core-shell nanoparticles on the optical absorption of Perovskite solar cells - Ullah, Ihsan; Saghaei, Hamed; Khan, Jahangeer; Shah, Said Karim (Optical and quantum electronics, 2022)
Among all the different methods to enhance the optical absorption of photovoltaic devices. The plasmonic effect is one the most prominent and effective ways to capture more incident light and also provide good carrier dynamic management. Here, we systematically introduce spherical gold nanoparticles (Au NPs) with different radii in the absorber layer of perovskite solar cells (PSCs). The overall enhanced optical absorption of around 14.20% and 20.02% is achieved for incorporated monolayer and bilayer Au NPs, respectively, in the active layer compared to the pure perovskite layer. Moreover, we employ the metal (Au)-dielectric (TiO 2 and SiO 2 ) nanoparticles in the absorber layer. The optical absorption increases as the core-shell size decreases. The optical absorption elevates in both Au@TiO 2 core-shell and Au@SiO 2 core-shell 17.5% and 3.5%, respectively. These results support superior separation and transfer of charge in the existence of plasmonic NPs. In addition, this study presents a very sophisticated approach to the optical enhancement of PSCs and thus helps to boost the overall photovoltaic device performance.